BAY 11-7082 Is a Broad-Spectrum Inhibitor with Anti-Inflammatory Activity against Multiple Targets - Jaehwi Lee; Man Hee Rhee; Eunji Kim; Jae Youl Cho (Mediators of Inflammation)
BAY 11-7082 (BAY) is an inhibitor of κB kinase (IKK) that has pharmacological activities that include anticancer, neuroprotective, and anti-inflammatory effects. In this study, BAY-pharmacological target pathways were further characterized to determine how this compound simultaneously suppresses various responses. Primary and cancerous (RAW264.7 cells) macrophages were activated by lipopolysaccharide, a ligand of toll-like receptor 4. As reported previously, BAY strongly suppressed the production of nitric oxide, prostaglandin E2, and tumor necrosis factor-α and reduced the translocation of p65, major subunit of nuclear factor-κB, and its upstream signaling events such as phosphorylation of IκBα, IKK, and Akt. In addition, BAY also suppressed the translocation and activation of activator protein-1, interferon regulatory factor-3, and signal transducer and activator of transcription-1 by inhibiting the phosphorylation or activation of extracellular signal-related kinase, p38, TANK-binding protein, and Janus kinase-2. These data strongly suggest that BAY is an inhibitor with multiple targets and could serve as a lead compound in developing strong anti-inflammatory drugs with multiple targets in inflammatory responses.